2012
DOI: 10.1016/j.cmet.2012.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Specific Deletion of TFAM Increases Mitochondrial Oxidation and Protects Mice against Obesity and Insulin Resistance

Abstract: Obesity and type 2 diabetes are associated with mitochondrial dysfunction in adipose tissue, but the role for adipose tissues mitochondria in the development of these disorders is currently unknown. To understand the impact of adipose tissue mitochondria on whole body metabolism, we have generated a mouse model with disruption of the mitochondrial transcription factor A (TFAM) specifically in fat. F-TFKO adipose tissue exhibit decreased mtDNA copy number, altered levels of proteins of the electron transport ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
175
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(187 citation statements)
references
References 51 publications
10
175
1
1
Order By: Relevance
“…Mitochondrial oxidative capacity was shown to be compromised in muscle-specific TFAM knockout mice, however these animals exhibited improved glucose clearance during a glucose tolerance test and maintained insulinstimulated glucose uptake in muscle [197]. TFAM knockout in adipose tissue was recently shown to protect against diet-induced obesity and insulin resistance, despite causing abnormalities in mitochondrial function [125]. Similar findings were reported in mice with liver or muscle-specific deletion of apoptosis-inducing factor.…”
Section: Rodent Studiessupporting
confidence: 71%
See 1 more Smart Citation
“…Mitochondrial oxidative capacity was shown to be compromised in muscle-specific TFAM knockout mice, however these animals exhibited improved glucose clearance during a glucose tolerance test and maintained insulinstimulated glucose uptake in muscle [197]. TFAM knockout in adipose tissue was recently shown to protect against diet-induced obesity and insulin resistance, despite causing abnormalities in mitochondrial function [125]. Similar findings were reported in mice with liver or muscle-specific deletion of apoptosis-inducing factor.…”
Section: Rodent Studiessupporting
confidence: 71%
“…Administration of thiazolidinediones promotes mitochondrial biogenesis in WAT in animals and humans, in conjunction with improved whole-body insulin sensitivity [46,123], suggesting that specific changes in WAT mitochondrial metabolism in obesity and T2D, may be imparting whole-body metabolic consequences. Indeed, recent work has shown adipose-restricted alterations in mitochondrial activity can have profound effects on global glucose and lipid homeostasis [124,125].…”
Section: White Adipose Tissuementioning
confidence: 99%
“…In line with our observations, PGC-1a knockout mice develop mitochondrial dysfunction, cold intolerance and obesity in the absence of change in UCP1 expression 16 . Increased mitochondrial oxidation in adipose tissue by Tfam knockout increases energy expenditure and protects mice against obesity and insulin resistance, also in a UCP1-independent manner 35 . 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of dysfunctional mitochondria in the development of type 2 diabetes has been highly controversial because mitochondrial dysfunction leads to the protection against obesity and insulin resistance in apoptosis-inducing factor 1 (AIF1)-, mitochondrial transcription factor A (TFAM)-, or PGC-1␣/␤-deficient mice (32,33,57). However, our data showed that CI dysfunction resulted in a decrease of the NAD ϩ /NADH ratio, the deactivation of SIRT1, an increased expression level of PTP1B, the inactivation of IR␤ and IRS-1, and insulin resistance (Fig.…”
Section: Discussionmentioning
confidence: 99%